2010
DOI: 10.1089/jamp.2009.0778
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Level of PDCD4 (Programmed Cell Death 4) Protein Activated Cell Proliferation in the Lung of A/J Mouse

Abstract: Background: Programmed cell death 4 (PDCD4), a protein that binds to eukaryotic initiation factor 4A (eIF4A), inhibits the initiation of translation. Although a number of tumor suppressors target transcription, Pdcd4 is the first suppressor targeting protein translation, and has also been suggested to function as a tumor suppressor gene in human cancer. The majority of tumor suppressors are mutationally inactivated, but the expression of Pdcd4 is downregulated with progression in a number of human cancer sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…An inverse correlation of PDCD4 and p-Akt expression has been reported in colorectal cancer tissue samples [33] . shRNA PDCD4 activated Akt pathway, leading to the increased expressions of p-Akt, mTOR and p70S6K in the lungs of mice [34] . Our results were in concordance to these findings and implied the involvement of p-Akt pathway in the regulation of PDCD4 in ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…An inverse correlation of PDCD4 and p-Akt expression has been reported in colorectal cancer tissue samples [33] . shRNA PDCD4 activated Akt pathway, leading to the increased expressions of p-Akt, mTOR and p70S6K in the lungs of mice [34] . Our results were in concordance to these findings and implied the involvement of p-Akt pathway in the regulation of PDCD4 in ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of CASC9 could downregulate PDCD4, while overexpression of CASC9 increased PDCD4 levels. PDCD4 is reported to be involved in apoptosis, proliferation and cell cycle [ 26 28 ]. Our previous work has also revealed that suppression of PDCD4 promotes G1/S transition of ESCC cells [ 24 ], which is consistent with present results in CASC9 knockdown cells.…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted by Wu et al (31) demonstrated the negative correlation between CASC9 and programmed cell death protein 4 (PDCD4) in ESCC. PDCD4 is a tumor suppressor gene that participates in the regulation of apoptosis, proliferation and the cell cycle (32)(33)(34). Wu et al (31) further proposed that CASC9 may downregulate PDCD4 expression by recruiting histone-lysine N-methyltransferase EZH2 to augment the proliferative ability of ESCC.…”
Section: Discussionmentioning
confidence: 99%